Machine Learning Approach for Fatigue Estimation in Sit-to-Stand Exercise - Aguirre, Andrés; Pinto, Maria J.; Cifuentes, Carlos A.; Perdomo, Oscar; Díaz, Camilo A; Múnera, Marcela (MDPI (Multidisciplinary Digital Publishing Institute), 2021)
Physical exercise (PE) has become an essential tool for different rehabilitation programs. High-intensity exercises (HIEs) have been demonstrated to provide better results in general health conditions, compared with low and moderate-intensity exercises. In this context, monitoring of a patients’ condition is essential to avoid extreme fatigue conditions, which may cause physical and physiological complications. Different methods have been proposed for fatigue estimation, such as: monitoring the subject’s physiological parameters and subjective scales. However, there is still a need for practical procedures that provide an objective estimation, especially for HIEs. In this work, considering that the sit-to-stand (STS) exercise is one of the most implemented in physical rehabilitation, a computational model for estimating fatigue during this exercise is proposed. A study with 60 healthy volunteers was carried out to obtain a data set to develop and evaluate the proposed model. According to the literature, this model estimates three fatigue conditions (low, moderate, and high) by monitoring 32 STS kinematic features and the heart rate from a set of ambulatory sensors (Kinect and Zephyr sensors). Results show that a random forest model composed of 60 sub-classifiers presented an accuracy of 82.5% in the classification task. Moreover, results suggest that the movement of the upper body part is the most relevant feature for fatigue estimation. Movements of the lower body and the heart rate also contribute to essential information for identifying the fatigue condition. This work presents a promising tool for physical rehabilitation.

El ejercicio físico (EF) se ha convertido en una herramienta imprescindible para diferentes programas de rehabilitación. Se ha demostrado que los ejercicios de alta intensidad (HIE) proporcionan mejores resultados en condiciones generales de salud, en comparación con los ejercicios de intensidad baja y moderada. En este contexto, el seguimiento del estado del paciente es fundamental para evitar condiciones extremas de fatiga, que pueden provocar complicaciones físicas y fisiológicas. Se han propuesto diferentes métodos para la estimación de la fatiga, tales como: monitoreo de parámetros fisiológicos del sujeto y escalas subjetivas. Sin embargo, todavía se necesitan procedimientos prácticos que proporcionen una estimación objetiva, especialmente para las HIE. En este trabajo, considerando que el ejercicio sit-to-stand (STS) es uno de los más implementados en rehabilitación física, se propone un modelo computacional para estimar la fatiga durante este ejercicio. Se llevó a cabo un estudio con 60 voluntarios sanos para obtener un conjunto de datos para desarrollar y evaluar el modelo propuesto. Según la literatura, este modelo estima tres condiciones de fatiga (baja, moderada y alta) mediante el monitoreo de 32 características cinemáticas STS y la frecuencia cardíaca de un conjunto de sensores ambulatorios (sensores Kinect y Zephyr). Los resultados muestran que un modelo de bosque aleatorio compuesto por 60 subclasificadores presentó una precisión del 82,5% en la tarea de clasificación. Además, los resultados sugieren que el movimiento de la parte superior del cuerpo es la característica más relevante para la estimación de la fatiga. Los movimientos de la parte inferior del cuerpo y la frecuencia cardíaca también aportan información esencial para identificar el estado de fatiga. Este trabajo presenta una herramienta prometedora para la rehabilitación física.
Keywords: Ejercicios terapéuticos; Exercise therapy; Frecuencia cardiaca; Heart rate; Tecnología de Kinect; Kinect technology; Sensores biomédicos; Biomedical sensors; Estimación de fatiga; Fatigue estimation; Kinect; Aprendizaje automático; Machine learning; Ejercicio físico; physical exercise; Rehabilitación física; Physical rehabilitation